Limes/limen. For a history of the notarial registers bindings as mediation spaces (12th-15th centuries) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The aim of the paper is to analyse the paradoxically ambiguous and hybrid nature – at the same time limes and limen – of the bindings of medieval notarial registers, through which it is possible to discern the extraordinary medieval notaries’ ability to manage materials, structures and spaces as well as their wide knowledge of forms, communicative languages and expressive styles.
Keywords: Bindings; Notarial Registers; Notaries; 12th-15th Centuries